FTIR and UV Visible Spectrophotometric Approach to Discriminate Leukemic Sera - Gunasekaran, S.; Natarajan, R.K.; Renganayaki, V.; Rathikha, R. (Asian Journal of Chemistry, 2010)
Blood being the chief circulatory medium in human body, participates in every functional activity by virtue of its circulation through every organ. Almost in all diseases the blood undergoes major changes in chemical and biochemical properties. The study of blood by spectroscopic techniques can be used not only for understanding the biological nature of the disease, but also for the diagnosis of the disease. In the present work, Fourier Transform Infra Red (FTIR) and UVVisible spectroscopic techniques are employed to study the spectral differences between a healthy serum and that affected with leukemia. The intensity ratio parameters (IRP) among the peaks are calculated in both the methods and it is found to be an indicator to differentiate a leukemic serum from the healthy one. Also to substantiate the findings, univariate statistical analysis has been made.